Geographical Variation in Physical Fitness Among Chinese Children and Adolescents From 2005 to 2014 - Dong, Yanhui; Chen, Manman; Song, Yi; Ma, Jun; Lau, Patrick W. C. (Frontiers in Public Health, 2021)
Introduction: To examine the geographical variation in change in the levels of physical fitness from 2005 to 2014 among Chinese children and adolescents. Methods: A total of 663,813 children 7 to 18 years of age with physical fitness data in 2005, 2010 and 2014, participated in the study. Physical fitness was assessed using six components, and their standardized scores were aggregated to form a summary physical fitness indicator (PFI). Results: Over the study period, there was an increase in the proportion of high PFI (from 15.3% in 2005 to 19.0% in 2014, Ptrend < 0.05) and a decrease in the proportion of low PFI (from 30.6 to 29.8%, Ptrend < 0.05). Children and adolescents in the eastern provinces of China showed a high proportion of high PFI with an increasing trend over time, while those in the western provinces had a high proportion of low PFI with a decreasing trend over time (P < 0.05). Conclusions: The comprehensive physical fitness among Chinese children showed an improved trend from 2005 to 2014. Region-specific interventions with priority policies could be useful to sustainably narrow geographical variation in Chinese children, especially in the western provinces.